The Prorenin and (Pro)renin Receptor: New Players in the Brain Renin-Angiotensin System? - Wencheng Li; Hua Peng; Dale M. Seth; Yumei Feng (International Journal of Hypertension)
It is well known that the brain renin-angiotensin (RAS) system plays an essential role in the development of hypertension, mainly through the modulation of autonomic activities and vasopressin release. However, how the brain synthesizes angiotensin (Ang) II has been a debate for decades, largely due to the low renin activity. This paper first describes the expression of the vasoconstrictive arm of RAS components in the brain as well as their physiological and pathophysiological significance. It then focus on the (pro)renin receptor (PRR), a newly discovered component of the RAS which has a high level in the brain. We review the role of prorenin and PRR in peripheral organs and emphasize the involvement of brain PRR in the pathogenesis of hypertension. Some future perspectives in PRR research are heighted with respect to novel therapeutic target for the treatment of hypertension and other cardiovascular diseases.